2012
DOI: 10.1017/s1755267212000462
|View full text |Cite
|
Sign up to set email alerts
|

First record of Mola ramsayi from the Sea of Oman, Sultanate of Oman

Abstract: The first record of the southern ocean sunfish Mola ramsayi in Omani waters is reported based on a single 916 mm total length specimen found stranded on the coasts of Sur City 193 km south of the Omani capital Muscat, 22835 ′ 10.22 ′′ N 59830 ′ 18.91 ′′ E. This account also represents the third northernmost record of a south ocean sunfish in the Indian Ocean. Morphometric and meristic data are provided and compared with those of 5 specimens caught off United Arab Emirates, Brazil and India. The southern ocean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 11 publications
(6 reference statements)
4
9
1
Order By: Relevance
“…A has been found only in the Pacific Ocean, around Japan, Taiwan, Australia, and the Galápagos Islands (Bass et al 2005;Yoshita et al 2009;Thys et al 2013), where Bass et al (2005) and Thys et al (2013) called it M. ramsayi. The present study confirmed that both of the specimens from Oman, which were first published as Mola ramsayi and Mola mola (Jawad et al 2012;Jawad 2013), are genetically and morphologically Mola sp. A.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…A has been found only in the Pacific Ocean, around Japan, Taiwan, Australia, and the Galápagos Islands (Bass et al 2005;Yoshita et al 2009;Thys et al 2013), where Bass et al (2005) and Thys et al (2013) called it M. ramsayi. The present study confirmed that both of the specimens from Oman, which were first published as Mola ramsayi and Mola mola (Jawad et al 2012;Jawad 2013), are genetically and morphologically Mola sp. A.…”
Section: Discussionsupporting
confidence: 88%
“…Owing to a dearth of recorded sightings and catch data of Mola sunfishes in the Indian Ocean (Pope et The two specimens from Oman were originally regarded as belonging to species because of apparent differences in their morphology (Jawad et al 2012;Jawad 2013), but the present study, based on both genetics and morphology, found them to be the same species (Table 2). The counts of the clavus fin rays and ossicles of these specimens in the previous studies (Jawad et al 2012;Jawad 2013) were lower than those in this study (Table 2). OMMSFC 1085 was identified as M. ramsayi by Jawad et al (2012) because of its supposed lack of a smooth band in the clavus, but we found such a smooth band in this specimen ( Fig.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations